x+(x+1)+(x+2)=48x+(x-1)+(x-2)=487×(43-x)+5x+15=10×(43-x)+(x+3)×7(x-3.6)÷4=(x+4.8)÷8(x+10)×4=(0.6x+10)×5

来源:学生作业帮助网 编辑:作业帮 时间:2022/12/02 16:50:17
x+(x+1)+(x+2)=48x+(x-1)+(x-2)=487×(43-x)+5x+15=10×(43-x)+(x+3)×7(x-3.6)÷4=(x+4.8)÷8(x+10)×4=(0.6x+10)×5

x+(x+1)+(x+2)=48x+(x-1)+(x-2)=487×(43-x)+5x+15=10×(43-x)+(x+3)×7(x-3.6)÷4=(x+4.8)÷8(x+10)×4=(0.6x+10)×5
x+(x+1)+(x+2)=48
x+(x-1)+(x-2)=48
7×(43-x)+5x+15=10×(43-x)+(x+3)×7
(x-3.6)÷4=(x+4.8)÷8
(x+10)×4=(0.6x+10)×5

x+(x+1)+(x+2)=48x+(x-1)+(x-2)=487×(43-x)+5x+15=10×(43-x)+(x+3)×7(x-3.6)÷4=(x+4.8)÷8(x+10)×4=(0.6x+10)×5
x=15
x=17
太简单了